THE IMPACT OF ISLAMIC RELIGIOUS EDUCATION LEARNING DURING THE COVID-19 ENDURE ON CLASS VIII STUDENTS OF STATE 1 GALING FIRST MIDDLE SCHOOL, ACADEMIC YEAR 2020/2021 - evi liana; Ubabuddin; Sri Sunantri (IJGIE (International Journal of Graduate of Islamic Education), 2021)
Islamic education subject in secular school is quite minimal in its duration. Generally, it takes only two credit hours per week in such kind of school. Due to the time allocation, it is clearly impossible to hand down student standard religious knowledge, attitude, and skills. Therefore, the school needs to find an alternative way to respond the needs of standard religious education in secular schools. Some of the implemented strategies are the religious extra-curricular program, extra hours for the subject, and integrated the religious messages in non-religious subjects. Religious teaching staff must also be upgraded in terms of the quality, either the subject matter enrichment or the instructional process. In addition, the instructional process needs optimal implementation. The evaluation should cover the cognitive, affective, and psychomotor areas. The three previously mentioned domain in Islamic education subject must be carefully and comprehensively assessed.